Investigation of combustion characteristics in a hydrogen-fueled scramjet combustor - Tian, Ye; Shi, Wen; Guo, Mingming; Liu, Yuan; Zhang, Chenlin; Le, Jialing (Acta astronautica, 2021)
The combustion characteristics of a hydrogen-fueled scramjet combustor were investigated experimentally and numerically. One nonreacting case (case 1), and two different equivalence ratio (ER) reacting cases (cases 2 and 3) were compared. The combustion process of each reacting case was divided into three phases. In the first phase, the monitor pressure in case 2 (ER = 0.1) reached a higher level due to the fuel injected before the hydrogen was ignited, whereas the change in case 3 (ER = 0.3) was the opposite, being less than that in the nonreacting flow. Almost all of the hydrogen in case 2 was in the front of the cavity, and that in case 3 was both throughout the whole cavity and near the top wall behind the cavity. In the second phase, the ignition times were about 0.010 s in case 2 and about 0.022 in case 3; a larger ER of hydrogen might be difficult to ignite. Finally, in the last phase, the hydrogen combustion was stable. The shock train in case 3 was pushed into the isolator, and the disturbing distance was about 0.08 m, in accordance with the wall pressure distribution. The higher static temperature in case 2 was mainly in the back of the cavity and that in case 3 was in the cavity shear layer, in line with the hydroxyl planner laser-induced fluorescence (OH-PLIF) results. The combustion mode in case 2 was supersonic combustion and that in case 3 was subsonic combustion. •Combustion characteristics were investigated in a supersonic combustor.•The whole combustion process could be divided into three parts.•Various measurements are used for better understanding combustion characteristics.•The ignition time for different ER reacting cases was measured.